2020
DOI: 10.3390/horticulturae6020022
|View full text |Cite
|
Sign up to set email alerts
|

Container Type and Substrate Affect Root Zone Temperature and Growth of ‘Green Giant’ Arborvitae

Abstract: Root zone temperature (RZT) in nursery containers commonly exceeds ambient temperature during the growing season, negatively impacting crop growth and quality. Black nursery containers absorb radiant heat resulting in excessive RZT, yet other types of containers and different substrates can moderate RZT. We conducted studies in Tennessee and Alabama to evaluate the effects of container type and substrate on RZT and growth of 'Green Giant' arborvitae (Thuja standishii × plicata 'Green Giant'). Trade gallon arbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…"Green Giant" arborvitae is considered a heat tolerant plant and readily adaptable to various soil types [21]. Nevertheless, results of the present study support previous work by Witcher et al [17] where "Green Giant" arborvitae grown in white containers grew larger and produced more biomass compared with black containers.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…"Green Giant" arborvitae is considered a heat tolerant plant and readily adaptable to various soil types [21]. Nevertheless, results of the present study support previous work by Witcher et al [17] where "Green Giant" arborvitae grown in white containers grew larger and produced more biomass compared with black containers.…”
Section: Discussionsupporting
confidence: 87%
“…Plant species such as "Green Giant" arborvitae (Thuja standishii × plicata 'Green Giant') may be considered heat tolerant and adaptable to various soil types yet can be sensitive to high RZT and reduced moisture level. For example, "Green Giant" arborvitae grew larger and produced more root biomass in white containers compared to black containers due to extended exposure to RZT over 38 • C [17]. In the same study, peatmoss-amended substrate resulted in larger plants due to increased volumetric water content (VWC) compared to pine bark alone.…”
Section: Introductionmentioning
confidence: 87%
“…Such unnatural soil temperatures are routinely observed in horticultural nurseries under ‘normal’ air temperatures and, as a result, could be expected to be higher in experiments where high‐temperature stress treatments are applied. To counteract such effects, it has been recently found that using light‐coloured or white pots containing substrate mixtures maximizing soil volumetric water content could help reduce root zone temperature by up to 7–8°C (Witcher, Pickens, & Blythe, 2020a, 2020b). Deploying field‐based experimental set‐ups : conducting in situ studies where the above‐mentioned environmental drivers are closely monitored will be particularly valuable to evaluate hypotheses and outcomes obtained based on controlled‐environment approaches.…”
Section: Recommendations For Future Researchmentioning
confidence: 99%
“…Such unnatural soil temperatures are routinely observed in horticultural nurseries under 'normal' air temperatures and, as a result, could be expected to be higher in experiments where high-temperature stress treatments are applied. To counteract such effects, it has been recently found that using light-coloured or white pots containing substrate mixtures maximizing soil volumetric water content could help reduce root zone temperature by up to 7-8 C (Witcher, Pickens, & Blythe, 2020a, 2020b.…”
Section: Recommendations For Future Researchmentioning
confidence: 99%
“…The effect of environment conditions (temperature, rainfall, altitude, soil types, hail) [5][6][7][8][9], nutritional strategies [5,6,[10][11][12][13][14], water (stress, salinity) [5,8,12,15], container substrate of cultivation [16] on yield, yield traits and quality were analyzed in different crops in an open field [8,9,13,14,17] and greenhouses [5][6][7][10][11][12]15,16].…”
Section: Special Issue Overviewmentioning
confidence: 99%